Exploring the Potential of the Cyber Notary Concept in the Framework of International Transaction Settlement - Lubis, Ikhsan; Siregar, Taufiq; Lubis, Duma Indah Sari; Lubis, Andi Hakim (Talenta Publisher, Universitas Sumatera Utara, 2024)
This article examines the potential of Cyber Notary in facilitating international transactions and the legal challenges involved. With increasing demand for swift and secure cross-border transactions, technologies like digital signatures and blockchain offer innovative solutions for faster document validation. Successful implementations of Remote Online Notarization (RON) in the United States and the eIDAS standard in Europe highlight their effectiveness in enhancing efficiency. In Indonesia, challenges such as regulatory inconsistencies, limited public trust in digital documents, and cybersecurity issues hinder adoption. While the Electronic Information and Transactions Law provides a legal basis for electronic documents, achieving international recognition remains a significant hurdle. This research uses a normative legal methodology with a comparative approach, analyzing Cyber Notary practices in different jurisdictions to uncover opportunities and obstacles. Strengthening regulations, improving digital infrastructure, and increasing public awareness are critical steps to realize Cyber Notary’s potential. If successfully implemented, Cyber Notary can facilitate efficient, secure, and legally recognized international transactions, advancing Indonesia’s role in the global digital economy.